DIFFUSION MECHANISMS OF MULTIPLE STRONTIUM SPECIES IN CLAY - Cole T.; Bidoglio G.; Soupioni M.; O'Gorman M.; Gibson N. (My University, 2000)
A mechanistic diffusion model for Sr in water-saturated clay (illite and kaolinite) is elaborated based on laboratory results. Both porewater and surface diffusion pathways are identified. Their relative importance is controlled by variable adsorption selectivity of Sr, associated with aqueous speciation. Conditional diffusion coefficients for Sr, obtained experimentally using three independent methods, average 1.05 +/- 0.12 x 10-7 cm2 s-1 from separate determinations at 5°C. Speciation, based on analytical data and stability constants, predicts total strontium (aqueous and/or adsorbed) to comprise ~ 90% free ion, Sr2+, in adsorption and diffusion experiments within pH ~ 8. Total distribution coefficient doubles in the pH range ~ 8 to ~ 8.5, doubling again between pH ~ 8.5 and ~ 9.5. Minor occurrence of an aquo-carbonate species, SrCO3(aq), significantly increases the total adsorption affinity of Sr for the clay above pH ~ 8.5. Adsorption is reversible with species distribution coefficient for SrCO3(aq) about 60 times higher than that for Sr2+. EXAFS spectroscopy indicates similar first hydration sphere coordination numbers and distances for Sr, both adsorbed to clay and as solutions of SrCl2 and SrCO3. Adsorption to clay surfaces occurs as weak outer sphere bonding, including intact hydration shells. A greater mass fraction of total Sr is adsorbed, supporting any contribution of surface diffusion to net transport. Heightened adsorption affinity of Sr, due to carbonate complexation, enhances possible mass transfer by surface diffusion. Model estimates of intrinsic diffusion coefficients, independent of tortuosity, are more than one order of magnitude lower for surface compared with porewater. Invoking surface diffusion implies retardation in overall transport rate, relative to porewater diffusion alone.